remember we can add or subtract only "like" terms
so we have to form common denominators for each type
(1/5)x^2 + (1/10)x^2 which is (3/10)x^2 ...... 1/5 + 1/10 =2/10+1/10
then
(-1/5)x - (1/2)x
= (-2/10)x - (5/10)x = (-7/10)x
and finally
-3/4 + 1/2
= -3/4 + 2/4
= -1/4
(1/5x^2-1/5x-3/4)+(1/10x^2-1/2x+1/2)
= (3/10)x^2 - (7/10)x - 1/4
Essay show all work. Add the following polynomials; (1/5x^2-1/5x-3/4)+(1/10x^2-1/2x+1/2)
I really need help and I am thankful for your time, some tutors just mess with your head and make you more confused,if I did not need you guys I would not be here so thanks again
2 answers
thank you once again